A typology of propagation of technology and social preferences in the process of economic development. Issue 4 (8th July 2014) - A. Haddad, Eduardo; R. Faria, Weslem; J.M. Guilhoto, Joaquim
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to look at the interplay of technology and social preferences in different stages of economic development. Design/methodology/approach – The authors use a set of input-output tables for 32 different countries, published by OECD. The tables refer to the period 1996-2001 and were consolidated in 48 sectors so that structural comparisons were possible through the use of techniques of decomposition used for comparing different economic structures in the context of partitioned input-output systems. Findings – The authors confirm that, for different levels of per capita GDP, technological change is an important element to drive growth. However, as an economy evolves, the data set also confirm that the composition of final demand, which reveals social preferences in a static way, moves away from agricultural and manufacturing to services activities. Such structural changes favor sectors with stronger value added multipliers, and stronger complexity found in higher income countries generates a force that helps driving income divergence. Research limitations/implications – Given the chosen methodological approach, the structural features revealed in this study remain to be empirically tested in growth models. Practical implications – The paper includes implications for the testing of growth models, suggesting there may be an association between movement into service sectors and higher growth, as modern service sectors have important spillovers on and from the manufacturing. Moreover, the way countries engage in global value changes may affect growth. Originality/value – Using a unique data set, this paper adds to the empirical literature on economic growth that looks closer at the distinction between the role of structural change and changes in composition ode demand.